Model Struktural Prediktif Kinerja Adaptif dan Study–Life Balance: Peran Kapabilitas Strategis Dinamis dengan Bapukung sebagai Sumber Daya Kultural: Structural Predictive Model of Adaptive Performance and Study–Life Balance the Role of Dynamic Strategic Capabilities with Bapukung as a Cultural Resource - Sigit Dwi Prabowo; Nila Cahya; Sila Rizqina; Muhammad Saufi; Dewi Sri Susanti (Anterior Jurnal, 2026)
The transition into a higher education environment often triggers academic pressure demanding optimal adaptive performance and a balance between study and personal life. Amidst modernization challenges, the local wisdom value of Bapukung holds strategic potential as an often-overlooked internal resource for self-management. This study aims to construct a predictive structural model to explain the mediating mechanism of dynamic strategic capabilities in the relationship between cultural affiliation and student performance outcomes. Data were collected via a survey of 81 first-year female students in South Kalimantan and analyzed using the Regularized Structural Equation Modeling method with the Least Absolute Shrinkage and Selection Operator penalty. This statistical approach was applied to perform simultaneous variable selection to generate precise parameter estimates within a limited sample size. Analysis results indicate that cultural affiliation significantly builds the capabilities of sensing, seizing, and reconfiguring resources. A crucial finding from the model selection is a unique role specialization: the reconfiguring capability dominantly determines adaptive performance, while the seizing capability exclusively determines study-life balance. This study concludes that local culture serves as a vital foundation for developing modern self-management competencies, in which mental flexibility is the key to academic achievement and decisiveness is the determinant of life well-being.